Intraoperative application of low-dose dexmedetomidine or lidocaine for postoperative analgesia in pediatric patients following craniotomy: a randomized double-blind placebo-controlled trial - Bao, Di; Wang, Yaxin; Xiong, Wei; Zhang, Di; Qiao, Lanxin; Zheng, Na; Li, Lu; Jin, Xu (Frontiers in Surgery, 2024)
Background Postoperative pain is a common occurrence in pediatric patients following craniotomy, often leading to negative outcomes. Intravenous dexmedetomidine and lidocaine are commonly used adjuvant medicines in general anesthesia to reduce perioperative opioid consumption and relieve postoperative pain in adults. While they show promise for use in pediatrics, the evidence of their application in pediatric craniotomy patients is limited. Therefore, we aimed to compare the effects of dexmedetomidine and lidocaine on postoperative pain in pediatric patients following craniotomy.We conducted a randomized, double-blind, single-center trial on children scheduled for craniotomy. The 255 recruited participants aged 1-12 years were randomly assigned to intraoperatively receive a loading intravenous dose of either dexmedetomidine 1 μg•kg -1 or lidocaine 2 mg•kg -1 or normal saline for 15 min followed by dexmedetomidine 0.5 μg•kg -1 •h -1 or lidocaine 1mg•kg -1 •h -1 or normal saline until the sutures of endocranium were completed. The primary outcome was the cumulative sufentanil consumption within 24 hours post-surgery.Results A total of 241 patients were included in the statistical analysis. The primary outcome did not show any significant differences among the three groups (median [IQR] lidocaine group: 3.